Función del Técnico de Anatomía Patológica en la Unidad de Valoración del Riesgo de Muerte Súbita - Sancho Jiménez, Jennifer; Abellán Pinar, Yolanda; Soler Liesa, Jose L.; Molina Aguilar, Pilar; Ortiz Criado, Jose M. (CorSalud, 2017)
Función del Técnico de Anatomía Patológica en la Unidad de Valoración del Riesgo de Muerte Súbita